1989
DOI: 10.1002/anr.1780321008
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of iC3b neoantigen expression in plasma from patients with systemic lupus erythematosus

Abstract: We studied the expression of an iC3b neoantigen (iC3b-NEO) in plasma from patients with systemic lupus erythematosus (SLE), by using a monoclonal antibody specific for iC3b/C3dg/C3d, to investigate the activation of the third component of complement in SLE. The plasma iC3b-NEO level in 40 untreated patients with active SLE was significantly higher than that in 36 normal subjects (mean & SD 31.5 -t 13.9 pglml versus 12.3 -+ 3.3 pg/ml; P C 0.001). The plasma iC3b-NEO level was highly correlated with clinical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Complement activation products (C3d, C3a, C4a, C5a, iC3, C4d, Bb, C5b-9, and erythrocyte CR1) are raised in active disease, [140][141][142][143] but assays to measure these molecules are not widely available and require special sample handling to a degree that makes routine clinical use impracticable.…”
Section: Complementmentioning
confidence: 99%
“…Complement activation products (C3d, C3a, C4a, C5a, iC3, C4d, Bb, C5b-9, and erythrocyte CR1) are raised in active disease, [140][141][142][143] but assays to measure these molecules are not widely available and require special sample handling to a degree that makes routine clinical use impracticable.…”
Section: Complementmentioning
confidence: 99%
“…In an attempt to improve the value of complement measurements in the assessment of disease activity, investigators have measured the levels of serum markers of complement activation, such as anaphylatoxin levels [24], C1r-C1s-C1 inhibitor complexes [18], C4d levels [25], iC3b or C3dg levels [26,27] and membrane attack complex levels [28,29]. Although there is evidence that measurement of these complement activation products correlates somewhat better with disease activity than measurement of total C4 and C3 levels [30-32], none of these assays has been widely adopted in clinical practice.…”
Section: Complement and Sle: The Clinical Observationsmentioning
confidence: 99%
“…The extremely short half‐lives of C3a and C3b may prevent their detection (since the sample processing time is shorter), while the longer half‐life of C3d may not reflect concurrent complement activation. Two prior studies utilizing enzyme‐linked immunosorbent assay (ELISA) to examine iC3b levels in SLE patients found that plasma and serum iC3b levels were increased in patients with active SLE compared to healthy controls. However, these data may have been confounded by in vitro activation of C3 , which may lead to artefactually elevated iC3b levels , thereby limiting past determinations of iC3b to serve as a useful biomarker of complement activation.…”
Section: Introductionmentioning
confidence: 99%